2015
DOI: 10.1039/c4sc02754j
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular prodrugs of ribavirin: towards a treatment for co-infection with HIV and HCV

Abstract: Macromolecular prodrugs of ribavirin were developed as blood safe formulations with capacity to fight inflammation and human immunodeficiency virus in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…Without doubt, examples of strong, pronounced effects of molar mass on the biomedical properties of polymers are numerous and importance of this factor should not be overlooked. In our own prior work, with regards to the delivery of RBV, we found that high molar mass restricted the polymer cell entry and in doing so limited the observed therapeutic effects [39,65]. Not disregarding the importance of these observations, the data of this study strongly suggest chemical structure of the polymer is a dominant factor in its properties (at least in the experiments presented in this study) whereas polymer chain length is of secondary importance.…”
Section: Degree Of Polymerization Vs Polymer Structuresupporting
confidence: 50%
See 1 more Smart Citation
“…Without doubt, examples of strong, pronounced effects of molar mass on the biomedical properties of polymers are numerous and importance of this factor should not be overlooked. In our own prior work, with regards to the delivery of RBV, we found that high molar mass restricted the polymer cell entry and in doing so limited the observed therapeutic effects [39,65]. Not disregarding the importance of these observations, the data of this study strongly suggest chemical structure of the polymer is a dominant factor in its properties (at least in the experiments presented in this study) whereas polymer chain length is of secondary importance.…”
Section: Degree Of Polymerization Vs Polymer Structuresupporting
confidence: 50%
“…In our past studies, we developed broad-spectrum antiviral agents based on macromolecular prodrugs (MP) of ribavirin. When conjugated to polymers, ribavirin did not accumulate in the red blood cells which in vivo is the main side effect of the drug [37][38][39]. MP of ribavirin broadened the therapeutic window of the drug (in vitro) [37] and were effective against diverse viruses such as HCV (in a replicon cell culture model), measles, and influenza, in the latter case revealing antiviral effects in chicken embryo model [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 While this provides a higher therapeutic window between antiviral activity and cytotoxicity, these systems do not provide complete release and usually results in a lower efficacy against HIV infectivity. [11][12][13][14] Recently, a macromolecular prodrug anti-HIV system was devised that was capable of a rapid intracellular triggered release of an antiviral drug. In this system, the AZT drug was attached through a self-4 immolative, disulfanyl ethylcarbonate linker between the drug and a methacrylate polymer side chain.…”
Section: Introductionmentioning
confidence: 99%
“…7 For these reasons, AZT is often not recommended for treatment for first-line treatment of HIV. 8 Release of antiretroviral drugs from nanogels, 9 hydrogels, 10 or polymer conjugates [11][12][13][14] have all provided viable options for prolonging the circulation half-life and alleviating the cytotoxic side effects. While these systems effectively prolong the action of the antiviral released, drug release mechanisms rely on the presence of bonds that are intermediately stable to hydrolysis, such as ester linkages, to attach the drug to the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Upon further investigation of the polymer charge effect, it became clear that poly-anionic macromolecules inhibit viruses extracellularly by denying them cell entry in the first place [ 35 , 36 , 37 , 38 ], while poly-cationic macromolecules, on the other hand, are complexed with the genetic material of the virus [ 39 ]. Moreover, macromolecules play an essential role in controlling the release, distribution, and nonselective accumulation of the conjugated drugs [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Macromolecular Prodrugsmentioning
confidence: 99%